The Framework of 3P-Based Secure eHealth-Information System - Kim, Deuk Hun; Kwak, Jin (2018 International Conference on Platform Technology and Service, PlatCon 2018, 2018)
As eHealth-Information is computerized and managed, sensitive eHealth-Information is targeted and leaked in terms of personal information. Accordingly, it is necessary to improve the security of the eHealth-Information system by analyzing the security threats according to the flow of each flow. In this paper, we refer to patient, hospital, pharmacy and management organizations as 3P, and based on this, we study framework for secure eHealth-Information system.
Keywords: Centralized data-base; Medical security; Mobile e-Prescription; Personal information; Security threats; Cloud-Based Centralized database system; eHealth-Information System; Medical security; Mobile e-Prescription